Combination of ultrasound power Doppler‐verified synovitis and seropositivity accurately identifies patients with early‐stage rheumatoid arthritis. (18th March 2019) - Kawashiri, Shin‐ya; Fujikawa, Keita; Nishino, Ayako; Takatani, Ayuko; Shimizu, Toshimasa; Umeda, Masataka; Fukui, Shoichi; Igawa, Takeshi; Koga, Tomohiro; Iwamoto, Naoki; Ichinose, Kunihiro; Tamai, Mami; et al.
Abstract: Aim: We conducted this retrospective study to identify objective and comprehensive diagnostic criteria for early‐stage rheumatoid arthritis (RA) that are based on ultrasound (US) and serologic findings. Method: From August 2014 to May 2016, we recruited 216 consecutive patients at Hospital 1 and 223 consecutive patients at Hospital 2 who were suspected to have RA and underwent US of bilateral hands. In the US of bilateral hands from 22 sites, the findings obtained by grayscale and power Doppler (PD) assessments were each graded on a semi‐quantitative scale from 0 to 3. We also examined the assessment of the novel outcome measures in rheumatology (OMERACT)‐European League Against Rheumatism (EULAR) combined power Doppler ultrasound score (ie the cPD score) and the Global OMERACT‐EULAR Synovitis Score. We used the US findings and the combination of US and serologic findings to evaluate the diagnostic performance of these modalities. Results: Seventy patients (32.4%) at Hospital 1 and 59 patients (26.5%) at Hospital 2 were diagnosed as having RA. The best‐balanced diagnostic performance at each hospital was achieved using a combination, such as (1) the presence of PD grade ≥2 articular synovitis or (2) the presence of PD grade ≥1 articular synovitis and serologic positivity, as well as by using (1) the presence of cPD grade = 3 or (2) a cPD grade ≥2 and serologic positivity. Conclusion: The combination of a PD assessment or the cPD score with the measurement of autoantibodies of rheumatoid factor and/or anti‐cyclic citrullinated peptide antibodies can accurately identify patients with early‐stage RA.